Pelatihan Pengembangan LKPD Berdiferensiasi dalam Kurikulum Merdeka Sebagai Upaya Peningkatan Profesionalitas Pendidik IPA SMP/MTs Se-Kabupaten Pringsewu - Hasnunidah, Neni; Jalmo, Tri; Lengkana, Dewi; Herlina, Kartini (Universitas Lampung, 2024)
SMP/MTs science educators in Pringsewu Regency face significant obstacles in implementing Independent Curriculum-based learning. One of the obstacles is related to educators' understanding and skills in developing differentiated LKPD that is in accordance with the basic competencies and learning objectives to be achieved. The aim of this training is to increase knowledge and insight about government policies and the theoretical basis of the Independent Curriculum as well as improve educators' abilities in compiling differentiated LKPD based on the Independent Curriculum. The method used in this training consists of workshops, lectures, discussions and questions and answers. The training participants were 30 SMP/MTs science educators in Pringsewu Regency who were accommodated in the MGMP. The data collected is in the form of initial and final test results as well as an assessment of skills in compiling LKPD. The data analysis was carried out descriptively qualitatively. The results of service activities show an increase in educators' understanding of differentiated SMP/MTs science LKPD based on the Independent Curriculum with final test results with good criteria increasing by 59.48% from initial test results with poor criteria. Educators' skills have increased, especially in compiling differentiated science worksheet worksheets based on the Independent Curriculum. Only some of the differentiated LKPD products which are the work of training participants are of sufficient quality (46%) and good (31%). Meanwhile, only a small portion of the LKPD quality is very good, poor or very poor (8%).Keywords: differentiated learning; independent curriculum; professionalism AbstrakPendidik IPA SMP/MTs di Kabupaten Pringsewu menghadapi kendala yang signifikan dalam mengimplementasikan pembelajaran berbasis Kurikulum Merdeka. Salah satu kendala terkait dengan pemahaman dan keterampilan pendidik dalam mengembangkan LKPD berdiferensiasi yang sesuai dengan kompetensi dasar dan tujuan pembelajaran yang ingin dicapai. Tujuan pelatihan ini adalah untuk meningkatkan pengetahuan dan wawasan tentang kebijakan pemerintah dan landasan teori tentang Kurikulum Merdeka serta meningkatkan kemampuan pendidik dalam menyusun LKPD berdiferensiasi berbasis Kurikulum Merdeka. Metode yang digunakan dalam pelatihan ini terdiri dari workshop, ceramah, diskusi dan tanya jawab. Adapun peserta pelatihan adalah 30 pendidik IPA SMP/MTs di Kabupten Pringsewu yang diwadahi dalam MGMP. Data yang dikumpulkan berupa hasil tes awal dan tes akhir serta penilaian keterampilan dalam menyusun LKPD. Analisis data tersebut dilakukan secara deskriptif kualitatif. Hasil kegiatan pengabdian menunjukkan adanya peningkatan pemahaman pendidik tentang LKPD IPA SMP/MTs berdiferensiasi berbasis Kurikulum Merdeka dengan hasil tes akhir dengan kriteria baik meningkat sebesar 59,48% dari hasil tes awal yang berkriteria kurang. Keterampilan pendidik meningkat terutama dalam menyusun LKPD IPA berdiferensiasi berbasis Kurikulum Merdeka. Produk LKPD berdiferensiasi yang merupakan hasil karya peserta pelatihan hanya sebagian yang berkualitas cukup (46%) dan baik (31%). Sementara itu, LKPD yang berkualitas baik sekali, kurang, dan kurang sekali hanya sebagian kecil saja (8%).Kata Kunci: kurikulum merdeka; pembelajaran diferensiasi; profesionalitas DOI: https://doi.org/10.23960/rp/v4i2.hal.16-31